2017
DOI: 10.1097/coc.0000000000000169
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Stereotactic Body Radiotherapy (SBRT) for Extracranial Oligometastases

Abstract: Radiation oncologists are increasingly using SBRT for OM. The main reason for not using SBRT for OM is a perceived lack of evidence demonstrating clinical advantages. These data strengthen the need for robust prospective clinical trials (ongoing and in development) to demonstrate clinical efficacy given the widespread adoption of SBRT for OM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 24 publications
0
84
0
Order By: Relevance
“…To address this, randomised clinical trials are required. A recent international survey of >1000 oncologists in 43 countries showed that of those using SBRT, >60% were planning on increasing SBRT use for oligometastatic disease, confirming how rapidly the technique has been accepted into standard practice despite the lack of randomised evidence [27]. It is timely that trials are conducted now, before clinical equipoise is lost.…”
Section: Discussionmentioning
confidence: 88%
“…To address this, randomised clinical trials are required. A recent international survey of >1000 oncologists in 43 countries showed that of those using SBRT, >60% were planning on increasing SBRT use for oligometastatic disease, confirming how rapidly the technique has been accepted into standard practice despite the lack of randomised evidence [27]. It is timely that trials are conducted now, before clinical equipoise is lost.…”
Section: Discussionmentioning
confidence: 88%
“…Dosimetric planning to multiple lesions receiving differing doses (45–50Gy) and fractionation (35) while irradiating the same organs-at-risk is discussed, particularly for metastases in close proximity (≤5cm). The benchmark case was selected to demonstrate the planning trade-offs required to satisfy protocol requirements for two nearby lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer patients with few metastases limited in number and distribution could potentially be cured if all visible tumors were ablated with radiotherapy or surgery. With the increasing availability of the technological advances enabling SBRT (2), the use of ablative radiotherapy to treat oligometastases is increasing (3). To date, several single arm trials using ablative radiotherapy to treat oligometastases have been conducted (48).…”
Section: Introductionmentioning
confidence: 99%
“…The question was systematically reviewed and the authors pointed to the absence of evidence and raised the possibility that this was 'wishful thinking' (6). Despite the absence of evidence for any ablative techniques for metastases, SABR/SBRT has been much publicised for treatment of oligometastatic disease in the last year (19)(20)(21).…”
Section: Stereotactic Ablative Radiation (Sabr) Therapy For Lung Metamentioning
confidence: 99%